Targeting for total water network. 1. Waste stream identification - Ng, Denny K.S. (Animo Repository, 2007)
Over the past decades, numerous research works have been dedicated to in-plant water reuse/recycle. After the opportunities for maximum water recovery are exhausted through water reuse/recycle, water flow rates may be further reduced with regeneration processes. Before wastewater is discharged to the environment, wastewater will be treated to meet the requirements given in the emission legislation. In this series of papers, an overall framework called the "total water network" is analyzed. A total water network consists of water reuse/recycle and water regeneration, as well as wastewater treatment for final discharge. Part 1 of this series of papers presents a new targeting procedure utilizing the recent developed graphical and algebraic approaches to identify individual wastewater streams that are emitted from a water network. As will be shown in Part 2 of the series, identification of the individual waste streams is necessary to investigate the interactions among different elements of the total water network. Two literature examples are solved to illustrate the proposed approaches. © 2007 American Chemical Society.